A new species of Schistura (Teleostei: Nemacheilidae) from the south-western lowlands of Sri Lanka - Sudasinghe, Hiranya (Zootaxa, 2018)
Schistura scripta, new species, is described from Nakiyadeniya in the south-western lowlands of Sri Lanka. It can be distinguished from all other congeners from Sri Lankan and peninsular India by the combination of the following characters: an incomplete lateral line with 53–76 pores, ending beneath the dorsal-fin base or slightly beyond; 7–13 post-dorsal bars; 7½ branched dorsal-fin rays; absence of an axillary pelvic lobe; and absence of a suborbital flap.